Physicochemical parameters and functional properties of flours from advanced genotypes and improved cassava varieties for industrial applications - Chimphepo, L. (University of Malawi, 2021)
Cassava has potential for many industrial uses, which provide an opportunity for more rewarding markets. Therefore, significant research on improved varieties, targeting industrial applications, is required as a possible approach to spur improvements in the value chain. In addition, the promotion of cassava for production, targeting industrial applications, requires information on yield and stability performance of cassava genotypes and varieties in a diverse range of environments. To this end, this study evaluated the physicochemical parameters and functional properties of ten (10) improved cassava genotypes for fast-tracking adaptable and preferred cassava genotypes for industrial use as well as the effect of interaction of genotypes and varieties with environment on such physicochemical parameters and functional properties. The genotypes were collected from a multi-location (Uniform yield Trial) trial of the IITA breeding program in Malawi. Their flour samples were analysed for various physicochemical parameters and functional properties compared with currently marketed High Quality Cassava Flour (HQCF). Results show that genotype effect on overall quality characteristics endearing to industrial applications was significant, allowing identification of industry preferred genotypes. Starch and amylopectin content are the major determinants of variability in the cassava flours' functional properties, such as water and oil absorption capacities, solubility, and swelling power. Overall, genotypes I020452 and I010040, and the released variety Sagonja have a high starch and amylopectin content, high bulk density, and all the analysed functional properties. These genotypes showed comparable/or superior functional properties to market HQCF. On the other hand, the results showed that environments (E) and genotypes (G) and their interaction (G x E) effects were highly significant(P < 0.001) in explaining the variance of the physcochemical parameters and functional properties. Environment played a major role in influencing dry matter (on fresh root weight basis), bulk density and solubility. However, genotype and environment interaction played a major role in influencing starch content, amylopectin content, swelling power, and WBC. Based on interaction principal component analysis of G x E, I010040, MM06/0045 and TMSL110080 genotypes and Mbundumali, Mpale and Sagonja varieties were the most selected for both improved stability and better response according to AMMI. I010040 showed higher levels of starch related properties (starch and amylopectin content, bulk density, OAC, solubility and swelling power) whereas Mbundumali is high yielded higher dry matter content (on fresh root weight basis) and also WBC and TMSL110080 was the highest yielding in dry matter content (on fresh root weight basis). Therefore, these cassava genotypes and varieties can be targeted for cultivation in wide range of environments in the semi-arid climates and similar agro-ecologies for production of high quality cassava flour (HQCF) and starch for various industrial applications.